THE CONSTRUCTION OF POLITICAL SATIRE ON THE UNITED STATES–IRAN CONFLICT IN TIKTOK VIDEO CONTENT - Annisa Dwi Tazkia; Roziana Febrianita (Adisam Publisher, 2026)
The escalation of the geopolitical conflict between the United States and Iran has contributed to global economic instability, including rising inflation and increases in the prices of essential commodities in Indonesia. In response to these pressures, members of the public have increasingly used TikTok to express their concerns through political satire. This study aims to analyze political satire narratives on TikTok concerning the impact of the United States–Iran conflict on Indonesia. Employing a qualitative approach based on Rodney H. Jones’s Digital Discourse Analysis framework, this study examines textual elements, context, actions and interactions, as well as ideology and power embedded in digital content. The findings indicate that content creators employ humor and multimodal texts to simplify complex geopolitical issues into an accessible form of politainment. Participatory audience interactions contribute to the formation of collaborative discourse, in which satirical content ideologically functions as a form of social catharsis and a psychological defense mechanism for the public amid economic pressures, while simultaneously serving as an indirect form of criticism. The study further demonstrates that social media transforms elite-oriented representations of geopolitical issues into a collaborative form of popular culture that supports collective psychological resilience in digital spaces.